ON THE HUMAN PROBLEM AND HUMAN CHARACTERISTICS IN THE TEACHINGS OF IBN SINA (Scientific journal of the Fergana State University, 2023)
In this article, it is stated that the first ideas about man appeared long before he came to the field of philosophy, that philosophical teachings about man and his nature started from ancient times and gradually developed, and that principles such as humanity in the scientific heritage of Ibn Sina are important in the education of children.